Beauty Is in the Eye of the Beholder: Factors Influencing Disparity in Perceptions of Breast Reconstruction Aesthetic Outcomes. Issue 1 (2nd May 2022) - Wu, Shannon S.; Duraes, Eliana F. R.; Scomacao, Isis; Morisada, Megan; Djohan, Risal S.; Bernard, Steven L.; Moreira, Andrea; Schwarz, Graham S.
Abstract : Background: Patient-reported outcomes are the primary measurement of breast reconstruction success, but results may be affected by nontechnical factors such as socioemotional determinants. Third-party observers provide an independent assessment of aesthetic outcomes. Factors associated with disparity between patient and observer perceptions of outcomes are not well understood. Methods: One hundred forty-seven patients underwent breast reconstruction at the authors' institution between 2009 and 2011, completed the BREAST-Q, and had photographs graded by a diverse panel using the Validated Breast Aesthetic Scale. Patient satisfaction with breasts scores that aligned with observer scores were categorized as group 2; patient satisfaction that exceeded observer scores were group 1; and those lower than observer scores were group 3. Statistical analysis was performed using SPSS, with values of p < 0.05 considered statistically significant. Results: Twenty-eight patients (19 percent) were categorized as group 1, 93 (63 percent) in group 2, and 26 (18 percent) in group 3. Median overall appearance was highest in group 3 (median, 4.0; interquartile range, 4 to 4) and lowest in group 1 (median, 3.0; interquartile range, 2 to 3) ( p < 0.001). Psychosocial, sexual, and physical well-being were significantly associated with disparity (group 1 or 3 status) ( p < 0.01). Satisfaction with outcomes, nipples, abdomen, and breasts were significantly associated with disparity. Factors not significantly associated with disparity include age, body mass index, autologous or implant-based, adjuvant therapies, and timing of reconstruction. Conclusions: Incongruously high patient satisfaction with breast reconstruction aesthetics relative to third-party perception of aesthetic outcomes is associated with high quality-of-life scores. Incongruously low patient satisfaction with breast cosmesis compared with higher third-party perceptions was associated with low quality-of-life scores. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.